Times series averaging and denoising from a probabilistic perspective on time-elastic kernels - Marteau, Pierre-Francois (Zielona Góra: Uniwersytet Zielonogórski)
In the light of regularized dynamic time warping kernels, this paper re-considers the concept of a time elastic centroid for a set of time series. We derive a new algorithm based on a probabilistic interpretation of kernel alignment matrices. This algorithm expresses the averaging process in terms of stochastic alignment "automata". It uses an iterative agglomerative heuristic method for averaging the aligned samples, while also averaging the times of their occurrence.
Keywords: time series averaging; time elastic kernel; dynamic time warping; hidden Markov model; classification; denoising